When did we begin to spell "heteros*edasticity" correctly? - Paloyo, Alfredo R. (Philippine Review of Economics, 2014)
Using digitized texts scanned by Google and subjected to optical character recognition, I show that heteroskedasticity overtook heteroscedasticity as the preferred spelling in 2001 and has continued to dominate, except for 2005, up to 2008. The latest trends indicate that writers are moving toward the k variant. However, for words such as homoskedasticity, heteroskedastic, and homoskedastic, the corresponding spellings using c are still overwhelmingly dominant, albeit slowly shifting.